Mendorong Ekonomi Kreatif dengan Produk Inovatif Ecoprint Menuju Desa Ramah Lingkungan Berkelanjutan di Desa Margajasa, Kabupaten Lampung Selatan - Andre Setiawan; Athaya Aulia Rannisa; Fitri Wahyu Niarseh; Muhammad Dzikri Rofa; Nadia Artha Aulia; Rakha Kumara Zaki; Jihan Fahiravita; Imam Mahmud; Laili Fadhila Banuwa (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of the creative economy has become one of the main drivers in improving community welfare, especially in rural areas. Margajasa Village, located in South Lampung Regency, has significant potential for developing an environmentally friendly creative economy. However, a lack of understanding and skills in creating innovative products remains a major challenge. To address this issue, a community service team initiated an educational and training program on ecoprint product development for local residents, including PKK members and village officials. This program utilized the Participatory Action Research (PAR) method through socialization and hands-on training. The results indicate an increased understanding among participants regarding the ecoprint concept and its business potential. Additionally, participants were able to create simple ecoprint products with the potential to generate additional income. This initiative is expected to serve as an initial step toward realizing a sustainable, eco-friendly village through a creative economy.